Modelling and performance testing of a digital over-current relay enhanced designed model - Sekhane, Hocine; Labed, Djamel; Labed, Mohamed Amir (Національний технічний університет "Харківський політехнічний інститут", 2022)
The over-current relay is widely used to protect distribution and transmission electrical systems against excessive currents occurring due to short circuit or overload conditions. Many works have been carried out in the field of models simulation design of digital over-current relays in the literature, but unfortunately many of them are more complex design models, have very slow execution time and only work in simple faults cases. Purpose. The purpose of this work is to present the performance of a modified and improved model of a digital over-current relay designed in Simulink/MATLAB environment with more simplified design, faster execution time, and able to operate under more complex fault conditions. Methodology. Before starting tests, modelling of over-current relay is presented in details, of which the basic logics of the proposed model to implement inverse and instantaneous characteristics are well explained. Afterwards, various tests are carried out for the performance analysis of the enhanced designed relay model in terms of: operating speed for eliminating faults that has arisen, ability to distinguish between a fault current and load starting current, capacity distinguish between real and temporary fault currents, the way to manage variable faults over time, and the degree of harmony between primary protection relay and back-up protection relay. Originality. The originality of our proposed work consists in the development and improvement of a digital over-current relay model designed in Simulink/MATLAB environment in such way that it becomes able to operate under new harsh test conditions. This developed designed model is implemented and applied in a 400V radial distribution power system with a load that causes a starting current. Results. The obtained values of simulation are compared with the theoretically calculated values and known existing models. The obtained results after various tests validate the good performance of our enhanced designed model.

Реле надструму широко використовується для захисту електричних систем розподілу та передачі від надмірних струмів, що виникають внаслідок короткого замикання або перевантаження. У літературі було виконано багато робіт у галузі моделювання цифрового реле надструму, але, на жаль, багато з них є більш складними моделями конструкції, з дуже повільним часом виконання, і вони працюють лише у випадках простих несправностей. Метою даної роботи є представлення продуктивності модифікованої та вдосконаленої моделі цифрового реле надструму, розробленої в середовищі Simulink/MATLAB, з більш спрощеною конструкцією, швидшим часом виконання та здатністю працювати в більш складних умовах несправностей. Методологія. Перед початком випробувань детально представлено моделювання реле надструму, з якої добре пояснено основні логіки запропонованої моделі для реалізації зворотних і миттєвих характеристик. Після цього проводяться різноманітні випробування для аналізу продуктивності вдосконаленої розробленої моделі реле з точки зору: швидкості роботи для усунення виниклих несправностей, здатності розрізняти струм несправності та пусковий струм навантаження, можливості розрізняти реальні та тимчасові струми несправності, спосіб управління змінними несправностями в часі та ступінь відповідності реле первинного захисту та реле резервного захисту. Оригінальність запропонованої нами роботи полягає в розробці та вдосконаленні моделі цифрового реле надструму, розробленої в середовищі Simulink/MATLAB таким чином, щоб вона стала здатною працювати в нових жорстких умовах випробувань. Ця розроблена модель реалізована та застосована у радіальної розподільчої енергосистемі 400 В з навантаженням, що викликає пусковий струм. Результати. Отримані результати моделювання порівнюються з теоретично розрахованими значеннями. Результати, отримані після різноманітних випробувань, підтверджують хорошу продуктивність нашої покращеної розробленої моделі.
Keywords: digital over-current relay; inverse and instantaneous characteristics; load starting current; primary protection; back-up protection; цифрове реле надструму; зворотні та миттєві характеристики; пусковий струм навантаження; первинний захист; резервний захист